2016
DOI: 10.3389/fpls.2016.01569
|View full text |Cite
|
Sign up to set email alerts
|

Pre-sowing Seed Treatment with 24-Epibrassinolide Ameliorates Pesticide Stress in Brassica juncea L. through the Modulation of Stress Markers

Abstract: The present experiment was designed to assess the effects of seed soaking with 24-epibrassinolide (EBR) on the physiology of Brassica juncea L. seedlings grown under imidacloprid (IMI) toxicity. Application of EBR increased the length of seedlings, dry weight, and pigment contents, polyphenols, total phenols, and organic acids under IMI toxicity. The expression of genes coding key enzymes of pigment, phenols, polyphenols, and organic acid biosynthetic pathways was also studied including CHLASE (chlorophyllase)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 63 publications
1
47
0
Order By: Relevance
“…The present study demonstrated that salinity stress can significantly reduce the chlorophyll content of apple seedlings, and exogenous BL treatment can recover the content to normal levels (Figure 2A). The recovery of chlorophyll contents after the exogenous application of BL might be due to the modulation of transcription and translation processes by BR signaling, which ultimately stimulates chlorophyll biosynthesis and inhibits the breakdown of chlorophyll molecules (Sharma et al, 2016;Dong et al, 2017). Moreover, the present study indicated that the photosynthetic rate of the apple seedlings was reduced by salt stress, and exogenous BL application significantly improved photosynthetic rate under salt stress ( Figure 2B).…”
Section: Discussionmentioning
confidence: 52%
“…The present study demonstrated that salinity stress can significantly reduce the chlorophyll content of apple seedlings, and exogenous BL treatment can recover the content to normal levels (Figure 2A). The recovery of chlorophyll contents after the exogenous application of BL might be due to the modulation of transcription and translation processes by BR signaling, which ultimately stimulates chlorophyll biosynthesis and inhibits the breakdown of chlorophyll molecules (Sharma et al, 2016;Dong et al, 2017). Moreover, the present study indicated that the photosynthetic rate of the apple seedlings was reduced by salt stress, and exogenous BL application significantly improved photosynthetic rate under salt stress ( Figure 2B).…”
Section: Discussionmentioning
confidence: 52%
“…Indeed, the exposure of plants to all types of stress often results in oxidative damage caused by an overproduction of reactive oxygen species (ROS), which include both molecular and non‐molecular forms, such as hydrogen peroxide (H 2 O 2 ), singlet oxygen ( 1 O 2 ), superoxide anions (O 2 ·− ) and hydroxyl radicals (·OH), which ultimately cause hindrance to vital processes like photosynthesis (Gill and Tuteja , Tomescu et al , Sharma et al , , Tang and Luo , Soares et al ). In order to counteract the negative effects of ROS, plants possess a powerful and efficient antioxidant system, composed of both enzymatic and non‐enzymatic players, which act synergistically to protect cells from oxidative imbalances (Sharma et al , , b, , Soares et al ). In fact, in situations where ROS production is increased, endogenous and/or exogenous NO plays a significant role in ROS detoxification and stimulates the antioxidant response by altering gene transcription and protein functions (Nabi et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The determination of organic acids was done by following the protocol described by Sharma et al (2016). The organic acids were extracted from 1 ml of the oven-dried samples by the addition of 0.5 N HCl (0.5 ml) and 0.5 ml of methanol.…”
Section: Organic Acid Determination By Gc-msmentioning
confidence: 99%